2018
DOI: 10.1108/dpm-07-2017-0169
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach to developing a neighbourhood-based resilience measurement framework

Abstract: Purpose -As disaster resilience activities are increasingly occurring at the neighbourhood level, there is a growing recognition in research and in practice of the contributions that community stakeholders can make in assessing the resilience of their communities. The purpose of this paper is to describe the process in deriving a disaster resilience measurement framework by soliciting the perspectives of stakeholders from urban neighbourhoods in two countries. The authors examined their community values, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Increasingly, these assessments highlight the importance of enhancing the resilience of the social environment, or “social resilience,” and complementing this with other physical or built mitigation measures as a means to enhance communities’ readiness to future hazard events (National Institute of Standards and Technology 2015). In particular, social capital—a component of social resilience—has been highlighted by nongovernment and government stakeholders as a key way to increase the resilience of individuals and communities (Kwok et al 2016; Kwok et al 2018). Lessons from past disasters such as the Kobe earthquake in Japan, Hurricane Katrina in the U.S. Gulf Coast, Hurricane Sandy in the eastern United States, and the Christchurch earthquakes in New Zealand underscore the important roles that social capital played in facilitating community disaster and recovery (Aldrich 2012b; Elliott, Haney, and Sams-Abiodun 2010; Nakagawa and Shaw 2004; Paton et al 2014; The Associated Press-NORC Center for Public Affairs Research 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, these assessments highlight the importance of enhancing the resilience of the social environment, or “social resilience,” and complementing this with other physical or built mitigation measures as a means to enhance communities’ readiness to future hazard events (National Institute of Standards and Technology 2015). In particular, social capital—a component of social resilience—has been highlighted by nongovernment and government stakeholders as a key way to increase the resilience of individuals and communities (Kwok et al 2016; Kwok et al 2018). Lessons from past disasters such as the Kobe earthquake in Japan, Hurricane Katrina in the U.S. Gulf Coast, Hurricane Sandy in the eastern United States, and the Christchurch earthquakes in New Zealand underscore the important roles that social capital played in facilitating community disaster and recovery (Aldrich 2012b; Elliott, Haney, and Sams-Abiodun 2010; Nakagawa and Shaw 2004; Paton et al 2014; The Associated Press-NORC Center for Public Affairs Research 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that social vulnerability indicators need to be context sensitive, and that future indicator development work could consider community objectives, such as knowledge and skills, economic wellbeing, housing, health, safety, social connectedness, civic participation, and population dynamics. Other studies in New Zealand have investigated factors relating to resilience to natural hazards, including describing resilience factors among New Zealand’s indigenous people, Māori, after the 2011 Christchurch earthquake [ 47 ], developing a national resilience index (incorporating system-level resilience factors) [ 48 ], and identifying resilience factors within selected communities, using qualitative research methods [ 49 ].…”
Section: Existing Vulnerability Framework and Indicatorsmentioning
confidence: 99%
“…Although community participation is considered an essential component of effective resilience planning to natural hazard-risks [41,42], only in recent years some studies have integrated scientific approaches with the active participation of the community, local planners, decision-makers, and actors of the civil society (e.g., [43][44][45][46][47]). The specific community perceptions of vulnerability and risk related to volcanic hazards have been investigated in former works (e.g., [48][49][50][51]) through "top-down" approaches.…”
Section: Introductionmentioning
confidence: 99%